The relevance of fish in the summer diet of the Antarctic fur seal (Arctocephalus gazella) at Hope Bay, Antarctic Peninsula and Stranger Point, South Shetland Islands - Descalzo, Mariana; Daneri, Gustavo Adolfo; Harrington, Ana; Negrete, Javier; Negri, Agustina; Corbalán, Aldo; Barrera Oro, Esteban (Polar Biology)
The fish incidence, particularly notothenioids and myctophids, in the diet of non-breeding male Arctocephalus gazella in the western Antarctic Peninsula (AP) region is widely variable according to the studied locality. We made a comparative diet analysis on 158 fecal samples collected in summer 2005 at Hope Bay (HB), AP and at Stranger Point (SP), South Shetland Islands (SSI). The frequency of occurrence of Antarctic krill Euphausia superba and fish as prey was similar at HB, whereas krill was predominant at SP. For each fish species identified based on the otoliths found, their relative importance in the diet was evaluated using the IRI index. Notothenioid fish prevailed at HB, Pleuragramma antarctica being the most important prey. Contrarily, the myctophids Gymnoscopelus nicholsi and Electrona antarctica predominated at SP. Both benthopelagic and pelagic fish species were represented at HB, while the latter were more important at SP. Demersal nototheniid species (e.g., Trematomus spp.) were scarcely represented and only at HB, which might be related to a preference of fur seals for the more abundant pelagic prey there. At SP, demersal nototheniids were not represented in the scats. The fish species consumption was higher in diversity at SP in comparison with HB but low in overlap between the two sites. We surmise that the differences found in the dietary composition of fur seals from both sites could be related to 1—different topographical and hydrological conditions associated to the study areas; 2—historical finfish fisheries, which took place during the late 1970s at the SSI, but not in the AP. Our findings are compared with studies from other localities of the AP and the Scotia Arc. Fil: Descalzo, Mariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de ...